Philosophical investigations - Wittgenstein, Ludwig 1889-1951; Anscombe, G.E.M. (Blackwell Publishing Ltd, 2001)
DESCRIPTIONThe Philosophical Investigations of Ludwig Wittgenstein (1889-1951) present his own distillation of two decades of intense work on the philosophies of mind, language and meaning.ABOUT THE AUTHORLudwig Wittgenstein - 1889 - 1951 - was an Austrian-British philosopher who taught at the University of Cambridge and is known as one of the most important philosophers of the 20th century. He worked in the areas of logic and the philosophy of mathematics, the mind and language. The majority of his writing was published after his death.